Hypothesis for renin-angiotensin inhibitor mitigation of COVID-19. (July 2021) - Sackin, Henry
Abstract: Preexisting hypertension is a known risk factor for severe COVID-19. Abnormal activation of RAS upregulates angiotensin II (Ang-II) and contributes to severe manifestations of COVID-19. Although RAS inhibitors (RASi) are a mainstay of antihypertensive therapy, they have been associated (in some animal studies) with an increase in angiotensin converting enzyme 2 (ACE2) receptors that facilitate cellular entry of the SARS-CoV-2 virus. Nonetheless, current medical practice does not recommend curtailing RASi to protect hypertensive patients from COVID. On the contrary, there is clinical evidence to support a beneficial effect of RASi for hypertensive patients in the midst of a COVID-19 pandemic, although the precise mechanism for this is unclear. In this paper, we hypothesize that RASi reduces the severity of COVID-19 by promoting ACE2-AT1R complex formation at the cell surface, where AT1R mediates the major vasopressor effects of Ang-II. Furthermore, we propose that the interaction between ACE2 and AT1R impedes binding of SARS-CoV-2 to ACE2, thereby allowing ACE2 to convert Ang-II to the more beneficial Ang(1–7), that has vasodilator and anti-inflammatory activity. Evidence for ACE2-AT1R complex formation during reduced Ang-II comes from receptor colocalization studies in isolated HEK293 cells, but this has not been confirmed in cells having endogenous expression of ACE2 and AT1R. Since the SARS-CoV-2 virus attacks the kidney, as well as the heart and lung, our hypothesis for the effect of RASi on COVID-19 could be tested in vitro using human proximal tubule cells (HK-2), having ACE2 and AT1 receptors. Specifically, colocalization of fluorescent labelled: SARS-CoV-2 spike protein, ACE2, and AT1R in HK-2 cells can be used to clarify the mechanism of RASi action in renal and lung epithelia, which could lead to protocols for reducing the severity of COVID-19 in both hypertensive and normotensive patients.